Research note sport tourism versus event tourism: Considerations on a necessary distinction and integration. Issue 2 (14th March 2020) - Schlemmer, Philipp; Barth, Michael; Schnitzer, Martin
Abstract: Interest in sport-related tourism increased perceptibly around the millennium, however, a comprehensive conceptual framework for a classification of sport (event) tourism is still missing. The predominant focus of sport tourism encompasses event-related touristic endeavors, such as mega sport events; however, an holistic approach to sport tourism suggests the need for further integration of other sub-areas such as nonevent-related components. This research note, therefore, provides a sport tourism perspective and a methodological approach to establishing the sport tourism cube as a necessary tool for the further distinction and integration of sport and event tourism. The research aim is, therefore, to build a foundation for further scientific research in sport tourism.